Associative Account of Self-Cognition: Extended Forward Model and Multi-Layer Structure - Sugiura, Motoaki (Frontiers in Human Neuroscience, 2013)
The neural correlates of “self” identified by neuroimaging studies differ depending on which aspects of self are addressed. Here, three categories of self are proposed based on neuroimaging findings and an evaluation of the likely underlying cognitive processes. The physical self, representing self-agency of action, body-ownership, and bodily self-recognition, is supported by the sensory and motor association cortices located primarily in the right hemisphere. The interpersonal self, representing the attention or intentions of others directed at the self, is supported by several amodal association cortices in the dorsomedial frontal and lateral posterior cortices. The social self, representing the self as a collection of context-dependent social-values, is supported by the ventral aspect of the medial prefrontal cortex and the posterior cingulate cortex. Despite differences in the underlying cognitive processes and neural substrates, all three categories of self are likely to share the computational characteristics of the forward model, which is underpinned by internal schema or learned associations between one’s behavioral output and the consequential input. Additionally, these three categories exist within a hierarchical layer structure based on developmental processes that updates the schema through the attribution of prediction error. In this account, most of the association cortices critically contribute to some aspect of the self through associative learning while the primary regions involved shift from the lateral to the medial cortices in a sequence from the physical to the interpersonal to the social self.